Assessing the Impacts of Exports, Gross Capital Formation, Imports, Gross National Income, and Inflations on New Zealand’s Growth Trajectory - Adamu, Ishiaka; Adeola, Kuforiji Abdulwasiu; Mtitu, Abubakar Ali; Arabzada, Sirajuddin (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2025)
This research investigates the impact of gross national income (GNI), gross capital formation (GCF), exports of goods and services (EXP), imports of goods and services (IMP), and inflation and consumer prices (INF) on economic growth (GDP) in New Zealand (NZ). The study employs various statistical tests such as; normality, serial correlation, heteroscedasticity, and multicollinearity to test whether the model fits the data and the test results show that the model is statistically feasible. The time series data were derived from the World Bank data indicators website in NZ using a purposive sampling technique for fifty-one (51) year period, from 1972 to 2022, and the data were analyzed through Eviews 10 software versions. The results of the regression analysis show that GNI, GCF, EXP, and IMP have positive and significant impacts on GDP, while INF has a negative and insignificant impact on GDP. The research contributes to the understanding of key indicators in enhancing economic growth in NZ. The findings of this research suggest that improving export, national savings, capital formation, importation of raw materials will contribute immensely to the economic growth of NZ. In addition, the research also suggests that inflation should be controlled, as it may hinder the country’s economic growth. Controlling inflation is essential to boosting income generation and economic productivity. However, future research should consider broader geographical contexts of different nations, increase sample size, and variables for a comprehensive understanding of factors influencing economic growth over time.